(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the intermittent labor contract model established by the 2017 Labor Reform. The author explores the dichotomy between the need for flexible labor laws and the risk of precariousness, examining the discontinuity of service provision and subordination. It concludes that, although the model serves specific sectors and may reduce informality, it requires constant vigilance from oversight bodies to prevent fraud against social rights. (Received: July 2025 | Accepted: September 2025).